Effects of Typified Propolis on Mutans Streptococci and Lactobacilli: a Randomized Clinical Trial - Anauate-Netto, Camillo; Marcucci, Maria Cristina; Paulino, Niraldo; Anido-Anido, Andréa; Amore, Ricardo; Mendonça, Sergio de; Borelli Neto, Laurindo; Bretz, Walter Antonio (Brazilian Dental Science, 2013)
Objective: The aim of this study was to determine in a randomized, double-blind, placebo-controlled clinical trial the effects of typified propolis and chlorhexidine rinses on salivary levels of mutans streptococci (MS) and lactobacilli (LACT). Methods: One hundred patients were screened for salivary levels of MS >100,000 CFUs/mL of saliva. All patients presented with at least one cavitated decayed surface. Sixty patients met entry criteria. Subjects were adults 18- 55 years old. After restoration of cavitated lesions patients were randomized to 3 experimental groups: 1) PROP-alcohol-free 2% typified propolis rinse (n = 20); 2) CHX- 0.12% chlorhexidine rinse; 3) PL-placebo mouthrinse. Patients rinsed unsupervised 15 mL of respective rinses twice a day for 1 min for 28 days. Patients were assessed for the salivary levels of MS (Dentocult SM) and LACT (Dentocult LB) at baseline, 7-day, 14-day, and at 28-day visits (experimental effects) and at 45-day visit (residual effects). General linear models were employed to analyze the data. Results: PROP was superior to CHX at 14-day and 28-day visits in suppressing the salivary levels of MS (p<.05). PROP was superior to PL at all visits (p < .01). The residual effects of PROP in suppressing the salivary levels of MS could still be observed at the 45-day visit, where significant differences between PROP and CHX (p < .05), were demonstrated. PROP was significantly superior than CHX in suppressing the levels of salivary LACT at the 28-day visit (p < .05).Conclusion: Typified propolis rinse was effective in suppressing cariogenic infections in caries-active patients when compared to existing and placebo therapies.